Mislocated fixations during reading and the inverted optimal viewing position effect - Nuthmann, Antje; Engbert, Ralf; Kliegl, Reinhold (Vision research (Oxford), 2005)
Refixation probability during reading is lowest near the word center, suggestive of an optimal viewing position (OVP). Counterintuitively, fixation durations are largest at the OVP, a result called the inverted optimal viewing position (IOVP) effect [Vitu, McConkie, Kerr, & O’Regan, (2001). Vision Research 41, 3513–3533]. Current models of eye-movement control in reading fail to reproduce the IOVP effect. We propose a simple mechanism for generating this effect based on error-correction of mislocated fixations due to saccadic errors. First, we propose an algorithm for estimating proportions of mislocated fixations from experimental data yielding a higher probability for mislocated fixations near word boundaries. Second, we assume that mislocated fixations trigger an immediate start of a new saccade program causing a decrease of associated durations. Thus, the IOVP effect could emerge as a result of a coupling between cognitive and oculomotor processes.